Impact of Capital Gains Tax on Stock Investment in Pakistan - Lodhi, Khalid Mahmood (Information Management and Business Review, 2013)
This study analyzes the impact of capital gains tax on stocks investment in Pakistan. Whenever there is an increase in the value of a capital asset realized over its cost it is termed as capital gain and the tax imposed thereof is called Capital Gains Tax. The study finds that levy of Capital Gains Tax results in lower volume of stock investment and lesser growth in assets/securities whereas the revenues have also declined as further investments have declined due to the fears of documentation of small investors by the tax authorities.